Critical notes on bamboos from Flores Island - Widjaja, Elizabeth; Larasati, Isti; Sukaesih, Yolan (Reinwardtia, 2025)
WIDJAJA, E. A., LARASATI, I. & SUKAESIH, Y. Y. 2025. Critical notes on bamboos from Flores Island. Reinwardtia 24(1): 41‒50. — Based on the results of extended field exploration, including the taxonomic study of bamboo growing in Flores, two new species, namely Dinochloa nigroviolacea and Gigantochloa kelimutuense will be described and illustrated. It was also observed that the Timorese black bamboo Gigantochloa lako, which has not been reported before from Flores, was found growing wild in the interior of Ende Regency. Furthermore, our studies indicated that Chloothamnus schmutzii should be reduced to synonymy of Chloothamnus reholttumianus, which grows wild and has spread from Ngada Regency to West Manggarai Regency; this species is also found in East Sumba and Sumbawa. The results of our observations indicate that at present there are 17 species of bamboo growing in Flores, belonging to Bambusa (4 species), Chloothamnus (1 species), Dendrocalamus (1 species), Dinochloa (2 species), Fimbribambusa (1 species), Gigantochloa (4 species), Phyllostachys (1 species), Schizostachyum (2 species), and Thyrsostachys (1 species). They can be distinguished using the key provided